The Challenges and Risks facing ICT in the Management and Operation of the Smart Grid - Tarek Mohammed Attia (Renewable Energy and Sustainable Development, 2019)
The Smart Grid integrates the traditional electrical power grid with information and communication technologies (ICT). Such integration empowers the electrical utilities providers and consumers, improves the efficiency and the availability of the power system while constantly monitoring, controlling and managing the demands of customers. Through smart grid, the power system becomes smart by communicating, sensing, control and applying intelligence. The Smart Grid is also kept the environment free from pollution; minimize the cost, effective operations, against all types of hazards and danger. Smart Grid is a huge complex network composed of millions of devices and entities connected with each other through wireless communications techniques including Home Area Networks (HANs) and Wide Area Networks (WANs). Such a massive network comes with many security concerns and vulnerabilities. In this paper, we highlight the complexity of the smart grid network and discuss the comparison between heterogeneous network. We discuss then the challenges that exist in securing the smart power grid and the countermeasures and solutions applied for information and communication networks to secure Smart Power Grid. We conclude by over viewing the key functions and benefits of using the Smart Gird technology and how this impacts on human livelihood, economy and the environment.